Introduction to information systems - O'Brien, James A. (New York McGraw-Hill/Iwin, 2005)
This book reflects the contemporary use of enterprise-wide business systems. New real-world case studies continue to correspond with this industry reality. The text's focus is on teaching the future manager the potential effect on business of the most current IT technologies such as the Internet, Intranets, and Extranets for enterprise collaboration, and how IT contributes to competitive advantage, reengineering business processes, problem solving, and decision-making.
Includes bibliographical references and indexes
Keywords: Quản trị kinh doanh